Outcome of patients with nonspecific pleuritis at thoracoscopy - Wrightson, J; Davies, H (2011)
PURPOSE OF REVIEW: The histological finding of pleural inflammation (pleuritis/fibrosis) is frequently found in pleural biopsies taken at thoracoscopy. This is a nonspecific finding, representing a common endpoint of many pleural conditions. Additional features, such as malignant cells, caseating granulomas and evidence of vasculitis, are required to make an aetiological histological diagnosis; in the absence of these features, the term 'nonspecific pleuritis/fibrosis' (NSP) is used. The cause of NSP is obscure and presents a particular dilemma: whether this apparently benign result represents a 'false-negative' sampling error in malignancy. RECENT FINDINGS: In a recent longitudinal follow-up study of 142 patients undergoing thoracoscopy, NSP was found in 31%. Of these, a likely cause for the NSP was found in 38% and malignancy occurred in 12%. These data were consistent with previous studies. SUMMARY: NSP is a histological diagnosis made in approximately 30-40% of patients with an undiagnosed exudative pleural effusion. The majority of cases adopt a benign course, although 8-12% may be subsequently found to have malignancy, particularly mesothelioma. In 25-91% no cause for the NSP is found; these patients are considered to have 'idiopathic pleuritis'. Prolonged follow-up, with occasionally further (usually more invasive) biopsies, is essential to rule out malignancy. © 2011 Lippincott Williams and Wilkins, Inc.